2016
DOI: 10.17583/rimcis.2016.2118
|View full text |Cite
|
Sign up to set email alerts
|

Female University Students Respond to Gender Violence through Dialogic Feminist Gatherings

Abstract: Within the framework of the "Free_Teen_Desire" research project led by the University of Cambridge and funded by the programme Marie Curie Actions 1 , a survey was conducted. Vignette-Test data for 127 female university students (ages 18-27 years) in Spain reveals that the wish to hook up with a violent young man significantly decreases after a gathering on the topic of the Mirage of Upward Mobility, a successful programme elaborated in Dialogic Feminism (Beck-Gernsheim, Butler & Puigvert, 2003). In the pre-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Third, the book employs a “language of desire” ( Flecha and Puigvert, 2010 ), which describes reality in terms of like, desire, emotions, and feelings, in contrast to a “language of ethics,” which analyzes reality in terms of what is good and what is bad. Other research has shown that using a “language of desire” - instead of a “language of ethics” alone - is much more effective for deeply understanding and discussing the coercive discourse and, particularly, for individuals having real freedom to decide, dismantling attraction to violent masculinities ( Puigvert, 2016 ). For the aforementioned reasons, Radical Love ( Gómez, 2015 ) aids in separating attractiveness and violence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the book employs a “language of desire” ( Flecha and Puigvert, 2010 ), which describes reality in terms of like, desire, emotions, and feelings, in contrast to a “language of ethics,” which analyzes reality in terms of what is good and what is bad. Other research has shown that using a “language of desire” - instead of a “language of ethics” alone - is much more effective for deeply understanding and discussing the coercive discourse and, particularly, for individuals having real freedom to decide, dismantling attraction to violent masculinities ( Puigvert, 2016 ). For the aforementioned reasons, Radical Love ( Gómez, 2015 ) aids in separating attractiveness and violence.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, research has shown that dialogs among friends can create expectations about behavior and gender in relation to the aggressive behavior of men ( Kimmel, 1996 ; Giordano, 2003 ), so conversations within peer groups are likely to be shaped by the coercive discourse and might reproduce it. Yet the fact that the coercive discourse, and different kinds of masculinities and emotions ( Ramírez Rodriguez et al, 2017 ) have been socially constructed opens up the possibility for the subjects to enact their own agency and free choice, and modify the influence of such discourse ( Gómez, 2015 ; Puigvert, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…All of the aforementioned prevention programs have been informed by particular research findings from psychology and other social sciences on gender violence among teens and have made it possible for adolescents to engage in specific transformations of their sexual-affective thought and behavior in ways that can protect them from experiencing violence in their intimate relationships. The case of the MEMO4LOVE project, the intervention research reported in this article, builds upon the various research projects on the topic of preventive socialization of gender violence (Valls et al, 2008;Gómez, 2015;Puigvert, 2016;, which have developed a strong body of evidence on the need to tackle the dominant coercive discourse in society to help youth escape from the social imposition of attraction models that link desire with violence and aggressiveness. The intervention program in the project adds to the current knowledge on prevention strategies for adolescents by focusing on the dominant coercive discourse, being a group-level intervention and school-based.…”
Section: Social Impact Of Psychology In the Area Of Gender Violencementioning
confidence: 99%
“…Another SEA is dialogic gatherings (DGs) in which students establish a dialogue around high-quality texts in areas such as literature, science, feminism, mathematics, music, art, or theology, among others [45][46][47][48]. In dialogic literary gatherings (DLGs), for instance, students read and discuss classic literature in an egalitarian dialogue, providing more opportunities to those who have participated less to contribute to the discussion, and hence overcome power interactions [49].…”
Section: The Impact Of Successful Educational Actions In Transformingmentioning
confidence: 99%